Contribution of a neopullulanase, a pullulanase, and an alpha-glucosidase to growth of Bacteroides thetaiotaomicron on starch. - D'Elia, J N (1996)
Bacteroides thetaiotaomicron, a gram-negative colonic anaerobe, can utilize three forms of starch: amylose, amylopectin, and pullulan. Previously, a neopullulanase, a pullulanase, and an alpha-glucosidase from B. thetaiotaomicron had been purified and characterized biochemically. The neopullulanase and alpha-glucosidase appeared to be the main enzymes involved in the breakdown of starch, because they were responsible for most of the starch-degrading activity detected in B. thetaiotaomicron cell extracts. To determine the importance of these enzymes in the starch utilization pathway, we cloned the genes encoding the neopullulanase and alpha-glucosidase. The gene encoding the neopullulanase (susA) was located upstream of the gene encoding the alpha-glucosidase (susB). Both genes were closely linked to another starch utilization gene, susC, which encodes a 115-kDa outer membrane protein that is essential for growth on starch. The gene encoding the pullulanase, pulI, was not located in this region in the chromosome. Disruption of the neopullulanase gene, susA, reduced the rate of growth on starch by about 30%. Elimination of susA in this strain allowed us to detect a low residual level of enzyme activity, which was localized to the membrane fraction. Previously, we had shown that a disruption in the pulI gene did not affect the rate of growth on pullulan. We have now shown that a double mutant, with a disruption in susA and in the pullulanase gene, pulI, was also able to grow on pullulan. Thus, there is at least one other starch-degrading enzyme besides the neopullulanase and the pullulanase. Disruption of the alpha-glucosidase gene, susB, reduced the rate of growth on starch only slightly. No residual alpha-glucosidase activity was detectable in extracts from this strain. Since this strain could still grow on maltose, maltotriose, and starch, there must be at least one other enzyme capable of degrading the small oligomers produced by the starch-degrading enzymes. Our results show that the starch utilization system of B. thetaiotaomicron is quite complex and contains a number of apparently redundant degradative enzymes.